2020
DOI: 10.1111/apt.15663
|View full text |Cite
|
Sign up to set email alerts
|

Gamma delta+ intraepithelial lymphocytes and coeliac lymphogram in a diagnostic approach to coeliac disease in patients with seronegative villous atrophy

Abstract: Summary Background The causes of seronegative villous atrophy can be grouped as coeliac or noncoeliac related. There is no consensus on how to approach subjects with seronegative coeliac disease. Aim To evaluate the accuracy of both an increase in CD3+ T‐cell receptor gamma delta+ (TCRγδ+) intraepithelial lymphocytes and coeliac lymphogram for the diagnosis of coeliac disease in patients with seronegative villous atrophy. Methods Sixty‐seven consecutive patients with seronegative villous atrophy were included.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 25 publications
3
32
0
Order By: Relevance
“…In fact, %TCRγδ + values are not influenced by the levels of serum anti-TG2 titters. Moreover, the results of other studies by our group, showing very high response rates to a GFD in patients with enteropathy of the CD spectrum, negative serology, and coeliac cytometric pattern, lend support to this hypothesis [ 12 , 28 ].…”
Section: Discussionsupporting
confidence: 69%
“…In fact, %TCRγδ + values are not influenced by the levels of serum anti-TG2 titters. Moreover, the results of other studies by our group, showing very high response rates to a GFD in patients with enteropathy of the CD spectrum, negative serology, and coeliac cytometric pattern, lend support to this hypothesis [ 12 , 28 ].…”
Section: Discussionsupporting
confidence: 69%
“…CD diagnosis was based on the presence of positive serology (either IgA anti-tissue transglutaminase -tTG- or IgA anti-endomysium antibodies -EmA-; IgG anti-tTG antibodies were used in case of selective IgA deficiency), Marsh 1 or Marsh 3 histological damage, and a clinical and serological remission after a GFD [ 1 ]. Seronegative Marsh 3 patients were diagnosed with CD based on the presence of both a coeliac pattern on IEL flow cytometry and a clinical and histological response to GFD [ 12 , 15 ]. Demographic data, clinical presentation, concomitant diseases, coeliac genetics (HLA-DQ2.5/DQ2.2/DQ8), duodenal histology, TCRγδ+ and CD3− IEL percentage, and clinical and histological response to GFD were recorded for all included patients.…”
Section: Methodsmentioning
confidence: 99%
“…A 2019 meta-analysis showed that the sensitivity of either an increase in TCRγδ+ cells or the presence of the coeliac lymphogram for CD diagnosis was >93% [ 11 ]. We have demonstrated the usefulness of this tool for the diagnosis of CD in seronegative villous atrophy [ 12 ]. Accordingly, TCRγδ+ IEL count assessed by flow cytometry has been advocated as a new and accurate diagnostic tool for doubtful CD cases, irrespective of the degree of mucosal damage, sex and age [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent times, robust flow cytometry methodology and quantification of gamma/delta (γδ) T cells have been proposed as complementary methods for aiding CD diagnosis and monitoring, particularly helpful in resolution of more difficult clinical cases ( 51 , 52 ). Analysis of an increase in γδ + T cells with a decrease in CD3 − IEL, the so-called “coeliac lymphogram,” was also shown to be useful in diagnosing seronegative CD cases ( 53 ). Such novel methods have proven superior to traditional serological monitoring methods.…”
Section: The Histological Lesion In CDmentioning
confidence: 99%